A Comprehensive Look at the Possibilities of Edible Insects as Food in Europe – a Review - Mlcek Jiri; Rop Otakar; Borkovcova Marie; Bednarova Martina (Polish Journal of Food and Nutrition Sciences)
Possibilities of edible insects use in European countries, are now an increasingly debated issue. Insects in Asian, African, Central American and South Central American cultures are mainly nutritional components. This review mainly describes the species of insects that are suitable as food in Europe and other developed countries. This comprehensive work addresses the issue of eating insects, especially considering the nutritionally important factors. Risks are also mentioned, as well as allergies, toxicity, and other aspects of the breeding and use of edible insects. Insects play and will play important roles in the future in various fields of research, exploitation, breeding, etc. This review provides a comprehensive current and future view of insects as a valuable foodstuff.